Postcranial functional morphology of Morotopithecus bishopi, with implications for the evolution of modern ape locomotion - MacLatchy, Laura; Gebo, Daniel; Kityo, Robert; Pilbeam, David (Journal of Human Evolution, 2000)
The large-bodied hominoid from Moroto, Uganda has until recently been known only from proconsulid like craniodental remains and some vertebrae with modern ape like features. The discovery of two partial femora and the glenoid portion of a scapula demonstrates that the functional anatomy of Morotopithecus differed markedly from other early and middle Miocene hominoids. Previous studies have consistently associated the vertebral remains with a short, stiff back and with orthograde postures. Although the proximal femur more closely resembles the femora of monkeys than of apes and suggests a moderate degree of hip abduction, the distal femur resembles those of extant large bodied apes and suggests a varied loading regime and an arboreal repertoire that may have included substantial vertical climbing. The femoral shaft displays uniformly thick cortical bone, beyond the range of thickness seen in extant primates, and signifies higher axial loading than is typical of most extant primates. The glenoid fossa is broad and uniformly curved as in extant suspensory primates. Overall, Morotopithecus is reconstructed as an arboreal species that probably relied on forelimb-dominated, deliberate and vertical climbing, suspension and quadrupedalism. Morotopithecus thus marks the first appearance of certain aspects of the modern hominoid body plan by at least 20 Ma. If the suspensory and orthograde adaptations linking Morotopithecus to extant apes are synapomorphies, Morotopithecus may be the only well-documented African Miocene hominoid with a close relationship to living apes and humans.
Keywords: Miocene; Hominoid evolution; Glenoid fossa; Femur; Vertebra